Trans-Cinnamaldehyde-Fighting Streptococcus mutans Using Nature - Zilefac Brian Ngokwe; Amit Wolfoviz-Zilberman; Esi Sharon; Asher Zabrovsky; Nurit Beyth; Yael Houri-Haddad; Dana Kesler-Shvero (MDPI AG, 2024)
Streptococcus mutans (S. mutans) is the main cariogenic bacterium with acidophilic properties, in part due to its acid-producing and -resistant properties. As a result of this activity, hard tooth structures may demineralize and form caries. Trans-cinnamaldehyde (TC) is a phytochemical from the cinnamon plant that has established antibacterial properties for Gram-positive and -negative bacteria. This research sought to assess the antibacterial and antibiofilm effects of trans-cinnamaldehyde on S. mutans. TC was diluted to a concentration range of 156.25-5000 μg/mL in dimethyl sulfoxide (DMSO) 0.03-1%, an organic solvent. Antibacterial activity was monitored by testing the range of TC concentrations on 24 h planktonic growth compared with untreated S. mutans. The subminimal bactericidal concentrations (MBCs) were used to evaluate the bacterial distribution and morphology in the biofilms. Our in vitro data established a TC MBC of 2500 μg/mL against planktonic S. mutans using a microplate spectrophotometer. Furthermore, the DMSO-only controls showed no antibacterial effect against planktonic S. mutans. Next, the sub-MBC doses exhibited antibiofilm action at TC doses of ≥625 μg/mL on hydroxyapatite discs, as demonstrated through biofilm analysis using spinning-disk confocal microscopy (SDCM) and high-resolution scanning electron microscopy (HR-SEM). Our findings show that TC possesses potent antibacterial and antibiofilm properties against S. mutans. Our data insinuate that the most effective sub-MBC of TC to bestow these activities is 625 μg/mL.